Data collection and analysis - Sapsford, Roger.; Jupp, Victor. (SAGE, 2006)
This work illustrates the range of techniques used in social research projects and considers the structure and logic of projects as well as the ethics and politics of research. This edition has new chapters on researching via the Internet and up-to-date examples of research in action.